2022
DOI: 10.3390/app12136508
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Optimum TBARS Conditions for Evaluation of Cow and Sheep Milk Oxidative Stability

Abstract: Having a complex fatty acid profile, milk is the subject of several oxidation processes that are different to those in other food matrices. Considering this, is important to appreciate the degradation status of milk using rapid and simple methods to quantify the main degradation products. The aim of this study was to adapt a simple and rapid method for determination of milk oxidative stability and to quantify malondialdehyde, one of the lipid oxidation products. Four parameters (trichloroacetic acid concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Nevertheless, studies examining milk showed that sheep milk contained a higher PUFA content (~25%) compared with cow milk, leading to a higher risk for lipid peroxidation and consequently to a higher MDA content. Indeed, the MDA content in sheep compared with cow milk was higher (13.40 vs. 8.07%) after 24h of storage at room temperature [ 49 ]. Moreover, the same researchers observed a strong positive correlation between PUFA and the index of lipid oxidation (MDA) [ 49 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, studies examining milk showed that sheep milk contained a higher PUFA content (~25%) compared with cow milk, leading to a higher risk for lipid peroxidation and consequently to a higher MDA content. Indeed, the MDA content in sheep compared with cow milk was higher (13.40 vs. 8.07%) after 24h of storage at room temperature [ 49 ]. Moreover, the same researchers observed a strong positive correlation between PUFA and the index of lipid oxidation (MDA) [ 49 ].…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, the MDA content in sheep compared with cow milk was higher (13.40 vs. 8.07%) after 24h of storage at room temperature [ 49 ]. Moreover, the same researchers observed a strong positive correlation between PUFA and the index of lipid oxidation (MDA) [ 49 ]. Additionally, the total antioxidant capacity, determined using ORAC assay, of low-fat pasteurized milk was significantly lower (13.624–13.984 μmol TE/l) than that of milk with a higher fat content (14.124–14.216 μmol TE/l) [ 50 ].…”
Section: Resultsmentioning
confidence: 99%
“…The TBARS assay is a rapid and convenient method to determine the levels of oxidative products derived from fatty acids in animal products ( Oancea et al, 2022 ). In agreement with the yield percentages, the TBARS values of CON remained consistent throughout the purification process involving various deodorants ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…For the quantitative analysis of MDA, the MDA standard was prepared by hydrolysis of TMP. 42 TMP standard solutions ranging from 0.36 to 10.8 μM were prepared with 0.1 M HCl. The solutions were hydrolyzed at 90 °C for 30 min.…”
Section: Methodsmentioning
confidence: 99%